2006
DOI: 10.1103/physrevb.73.125338
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the equations-of-motion technique for quantum dots

Abstract: The equations-of-motion (EOM) hierarchy satisfied by the Green functions of a quantum dot embedded in an external mesoscopic network is considered within a high-order decoupling approximation scheme. Exact analytic solutions of the resulting coupled integral equations are presented in several limits. In particular, it is found that at the particle-hole symmetric point the EOM Green function is temperature-independent due to a discontinuous change in the imaginary part of the interacting self-energy. However, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(146 citation statements)
references
References 47 publications
8
137
0
1
Order By: Relevance
“…56 In this appendix we derive the retarded Green's function to be used for the calculation of the differential conductance. For that purpose we employ the equation of motion technique [48][49][50][51] and in particular the truncation schemes proposed in Refs. 53 and 54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 In this appendix we derive the retarded Green's function to be used for the calculation of the differential conductance. For that purpose we employ the equation of motion technique [48][49][50][51] and in particular the truncation schemes proposed in Refs. 53 and 54.…”
Section: Discussionmentioning
confidence: 99%
“…We consider both cases in which the spin current is either driven by an external source (and therefore constant) or driven by the same electrode (and therefore voltage dependent). By using the equation of motion techniques [48][49][50][51] and comparing various truncation methods to obtain a consistent picture, we show that the Kondo ground state depends sensitively on the spin polarization of the electrode and the spin accumulation that it generates. We investigate both the spin-resolved spectral density of the localized spin and the nonlinear conductance.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method has limitations in the Kondo regime, particularly in the particle-hole symmetric case, for which the Green's function is indepedent of temperature. [69] Instead, second-order perturbation theory in U predicts a fading of the peak with increasing V ds without splitting. It has been suggested that terms of order U 3 and U 4 might cause the peak to split.…”
Section: Introductionmentioning
confidence: 99%
“…However, our interest for the moment is to take a step further and include Kondo correlations. We follow the calculation of Lacroix [67] and Kashcheyevs et al [68] and extend the EOM scheme by computing the evolution of these higher-order correlators:…”
Section: Appendix B: Equation Of Motion Beyond Hartree-fockmentioning
confidence: 99%
“…New higher-order correlators are generated in the process. Then, in order to obtain a solvable system of differential equations, we consider the approximation proposed by Mattis [68,69]:…”
Section: Appendix B: Equation Of Motion Beyond Hartree-fockmentioning
confidence: 99%